The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1207/s15324826an1003_04
|View full text |Cite
|
Sign up to set email alerts
|

Premorbid Intellectual Functioning, Education, and Brain Size in Traumatic Brain Injury: An Investigation of the Cognitive Reserve Hypothesis

Abstract: Cognitive reserve theories have been postulated in an attempt to explain individual differences in functional outcome following cerebral insult or disease. These theories suggest that higher education and psychometric intelligence may preserve functional capacity regardless of injury or disease severity. This study investigated cognitive reserve in 25 participants with traumatic brain injury (TBI) using high-resolution magnetic resonance imaging (MRI) analyses. We examined the relationships between total intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
141
4
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 250 publications
(161 citation statements)
references
References 63 publications
14
141
4
2
Order By: Relevance
“…We analyzed these outcomes with intelligence and memory divided them into subtypes. Cognitive intelligence and memory reserves are consistent with the prevailing clinical assumption that greater premorbid intellectual functioning is related to better outcome following TBI 11) . This theory suggests that higher education level and intelligence may preserve functional capacity regardless of injury or disease severity 11) .…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…We analyzed these outcomes with intelligence and memory divided them into subtypes. Cognitive intelligence and memory reserves are consistent with the prevailing clinical assumption that greater premorbid intellectual functioning is related to better outcome following TBI 11) . This theory suggests that higher education level and intelligence may preserve functional capacity regardless of injury or disease severity 11) .…”
Section: Discussionsupporting
confidence: 82%
“…Cognitive intelligence and memory reserves are consistent with the prevailing clinical assumption that greater premorbid intellectual functioning is related to better outcome following TBI 11) . This theory suggests that higher education level and intelligence may preserve functional capacity regardless of injury or disease severity 11) . Some studies have demonstrated that individuals with fewer years of education may be more vulnerable to the functional impact of TBI on intelligence quotient (IQ) outcome, regardless of the injury severity or degree of structural brain damage 11,13) .…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This pattern has been observed across a wide range of brain pathologies, including moderate to severe traumatic brain injury [9], cerebrovascular disease [10], hepatitis C [11], and AD [12]. Overall, a strong body of research has found support that intellectual ability, education, and occupational attainment are associated with cognitive reserve [7,[11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 90%
“…These deficits can be short-or longterm and are thought to be influenced by several factors, including age at injury, premorbid IQ, and the level of education attained by the individual ). Satz (1993 proposed a theory of cognitive reserve as a possible explanation for this heterogeneity of cognitive changes seen following TBI, and subsequent research has shown support for the theory (Ropacki & Elias, 2003;Kesler, Adams, Blasey, & Bigler, 2003).…”
Section: Overview Of the Literaturementioning
confidence: 99%